Compressed natural gas (CNG) tank analysis and testing [electronic resource] - Hamlin Anak Simph, 1987- (2010)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2010